Plan de marketing para el taller de servicios Hi-speed Tecnología Automotriz Integral, de la ciudad de Riobamba - Hidalgo Carrera, Xavier Mauricio (2015)
Technology Integral Automotive, Riobamba" was developed in the city of Riobamba, with the general objective to develop a marketing plan in order to improve economic and competitive development of the workshop, as the marketing plan is an essential tool for any organization as it facilitates the service and it is very risky to try to make a business succeed without having developed a marketing plan. Research on "Marketing Plan for Services Workshop HI-SPEED The research took into account the materials and methods such as inductive, deductive, analytical and research techniques such as direct observation, the manager of the workshop survey a survey conducted at 12 people including administrative and technical workshop were used and 310 excreta made to external customers are there in the shop. The results which begins with its historical background, organizational structure etc., then part detailing the internal and external analysis Workshop Services Automotive Technology HI-SPEED Integral, of Riobamba, then internal factors as performed are the strengths and weaknesses giving a weighted value of 2.98 which means that the workshop had more strength than weakness and external factors are the threats and opportunities in which a weighted value of 2.93 which means it was found that the workshop has more opportunities in the external environment and the threats do not harm, then the SWOT matrix and the matrix of criteria for high impact and assessment with their respective percentages is made, based on the results I have obtained the discussion, in which developed a Marketing Plan proposal to enhance entrepreneurship Workshop Services Automotive Technology HI-SPEED Integral, city of Riobamba in this consists the objectives for the workshop, which are: 1. Implement machine with latest generation technology to provide quality service to customers to become the leader workshop on the market for the following year. 2. Opening a branch to expand coverage in the local market and better positioning workshop in Riobamba. 3. Make an advertising plan in order to disclose the services rendered in workshop Riobamba. 4. Apply to personal training in order to achieve provide better service to customers to become a leader workshop on the market for the following year. Lastly most important conclusions of the investigation with their respective recommendations, the most important situations in the application obtained from the analysis of all the research work, so that the manager take the necessary corrective measures for their entity described; Bibliography, is the part where you have to know the sources of information used in the development of this work and last are the Annexes